Stress and the Psychological Impact of the COVID-19 Pandemic on Frontline Obstetrics and Gynecology Providers - Bogaert, Kelly C.; Lieb, Whitney E.; Glazer, Kimberly B.; Wang, Eileen; Stone, Joanne L.; Howell, Elizabeth A. (American Journal of Perinatology, 2022)
Objective The coronavirus disease 2019 (COVID-19) pandemic rapidly overwhelmed global health care systems in 2020, with New York City (NYC) marking the first epicenter in the United States. High levels of stress amongst health care workers have been reported in pandemics, but less is known about stress amongst Obstetrics and Gynecology (OB/GYN) providers. We sought to describe levels of stress, anxiety, depression, and other aspects of mental health among OB/GYN health care workers during the first wave of the COVID-19 pandemic.Study Design We conducted an anonymous cross-sectional electronic survey of a wide range of OB/GYN clinicians in a large NYC hospital system in the spring of 2020. We used both original survey questions and validated screening tools to assess stress, anxiety, depression, and burnout. We calculated median scores for these tools and compared median score between provider types. We also adapted questions on pandemic-related stressors from the MERS and SARS pandemics to fit the context of the COVID-19 pandemic and OB/GYN providers.Results A total of 464 providers met study inclusion criteria, and 163 providers completed the survey (response rate = 35.1%). Approximately 35% of providers screened positive for anxiety and 21% for depression. Scores for depression, burnout, and fulfillment varied by provider type, with nurses scoring higher than physicians (p <0.05). The majority of respondents reported stress from pandemic and OB-specific stressors, including the possibility of transmitting COVID-19 to friends and family (83.9%, [95% confidence interval or CI 78.0–89.8%]), uncertainty regarding the pandemic's trajectory (91.3% [86.7–95.8%]), and frequent policy changes on labor and delivery (72.7% [65.1–80.3%]).Conclusion OB/GYN providers reported high levels of stress during the COVID-19 pandemic. The stress of caring for laboring patients during a pandemic may disproportionately affect nurses and trainees and highlights the need to provide interventions to ameliorate the negative impact of a pandemic on the mental health of our OB/GYN health care workers.Key Points
Keywords: anxiety; burnout; COVID-19; depression; OB/GYN; pandemic; psychological distress; stressors